2014
DOI: 10.1002/eji.201343946
|View full text |Cite
|
Sign up to set email alerts
|

Viral inoculum dose impacts memory T‐cell inflation

Abstract: Memory T-cell inflation develops during certain persistent viral infections and is char-Keywords: CD8 + T cells r CMV r Memory T-cell inflation r T-cell activation r Viral immunity Additional supporting information may be found in the online version of this article at the publisher's web-site

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 53 publications
9
94
0
Order By: Relevance
“…The cell phenotype is once again tightly maintained. Data with similar implications are obtained by experiments in the MCMV model, where the populations expanded by low‐dose infection can be further boosted (and driven toward a more differentiated phenotype) in response to reinfections 49, 68, 69…”
Section: What Is Memory Inflation Now?supporting
confidence: 60%
“…The cell phenotype is once again tightly maintained. Data with similar implications are obtained by experiments in the MCMV model, where the populations expanded by low‐dose infection can be further boosted (and driven toward a more differentiated phenotype) in response to reinfections 49, 68, 69…”
Section: What Is Memory Inflation Now?supporting
confidence: 60%
“…Recently, it was shown that a low-dose inoculum of MCMV results in a severely hampered inflation of memory T-cells (Redeker et al, 2014), suggesting that the amount of virus is also a determinant of memory inflation. While it is generally accepted that systemic infection occurs during congenital HCMV infection by transfer of the virus through the placenta, infections after birth most likely occur via mucosal routes.…”
Section: Discussionmentioning
confidence: 99%
“…5), our data imply that latent viral load in the spleen, rather than in the lungs, predicts the magnitude of memory inflation, consistent with the recent observation that CMV-specific T-cells proliferate in the spleen of latently infected mice upon i.p. infection (Redeker et al, 2014). We focused in our study on prototypical inflationary epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, it has been shown that viral inoculum dose impacts the degree of CMV-specific memory T cell inflation and the phenotype of memory subsets (Redeker et al 2014). Of note, the studies to date that explore the relationship between immunosenescence and the size of the CMV-specific T cell response in humans have considered mainly interferon-γ (IFN-γ) secretion in response to a restricted number of target proteins, especially UL83 or UL123.…”
Section: T Cell Phenotypesmentioning
confidence: 99%